How does the Covid-19 pandemic affect regional labor markets and why do large cities suffer most? - Silke Hamann; Annekatrin Niebuhr; Duncan Roth; Georg Sieglen (Journal of Regional Science, 2023)
We estimate the spatially heterogeneous effects of the coronavirus disease 2019 pandemic on labor market dynamics in Germany until December 2021. While initially slightly stronger in rural regions and large agglomerations, adverse effects quickly become more pronounced and persistent in large agglomerations compared to all other region types. We ascribe the larger impact of the pandemic in large agglomerations to two factors. First, a combination of a higher share of skilled workers and jobs suitable for working from home is positively related to an increased inflow rate into unemployment. We argue that local spillover effects from reduced product market demand in large cities caused by changes in behavior such as working from home or online shopping are a possible explanation. Second, some of our results suggest that a lower outflow rate out of unemployment is associated with a higher precrisis unemployment rate in large agglomerations. This might reflect the less favorable composition of unemployment in large cities, which reduces the probability of transitions into employment during crises.
Keywords: 320; agglomerations; Covid-19 pandemic; employment; labor market flows